2018
DOI: 10.1111/dom.13274
|View full text |Cite
|
Sign up to set email alerts
|

Role of bicarbonate supplementation on urine uric acid crystals and diabetic tubulopathy in adults with type 1 diabetes

Abstract: Uricosuria and crystallization are increasingly recognized risk factors for diabetic tubulopathy. This pilot clinical trial aimed to determine the acute effect of urinary alkalinization using oral sodium bicarbonate (NaHCO ) on UA crystals in adults with type 1 diabetes (T1D). Adults with T1D, ages 18 to 65 years (n = 45, 60% female, HbA1c, 7.5 ± 1.2%, 20.2 ± 9.3 years duration) without chronic kidney disease (eGFR ≥60 mL/min/1.73 m and albumin-to-creatinine ratio < 30 mg/g) received 2 doses of 1950 mg oral Na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…The benefit of AP may be by blocking UA synthesis, whereas sodium BC appeared to facilitate urinary excretion of UA, therefore, reducing its systemic and renal concentrations. In this regard, there is evidence that BC supplementation reduced UA urine crystallization in diabetic patients along with tubular injury [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The benefit of AP may be by blocking UA synthesis, whereas sodium BC appeared to facilitate urinary excretion of UA, therefore, reducing its systemic and renal concentrations. In this regard, there is evidence that BC supplementation reduced UA urine crystallization in diabetic patients along with tubular injury [13].…”
Section: Discussionmentioning
confidence: 99%
“…Both effects favor UA crystallization in kidney tubules inducing an inflammatory reaction and AP has also proved to attenuate the acute kidney damage caused by experimental rhabdomyolysis [12]. Likewise, bicarbonate (BC) therapy, by virtue of increasing urine pH, can reduce urate crystalluria that might be important in inducing local injury [13]. However, while urate crystalluria can activate inflammasomes [14], which has been regarded as a mechanism to induce inflammation, apoptosis and kidney injury in acute rhabdomyolysis [15], there is also some data that soluble UA can also activate inflammasomes and can also induce release of chemokines that can induce a local inflammatory response [14].…”
Section: Introductionmentioning
confidence: 99%
“…However, average weight in the lowest SUA quintile was only 69 kg, compared to the average weight for the study of 80 kg [81], so the nutritional status of the lowest SUA quintile in this study is open to question. Similarly, in a study of 45 Type 1 diabetics, ranging in age from 18 to 65 years, the fasting mean SUA value was 4.1 ± 0.9 mg/dl [82]. This low SUA value may reflect undernourishment in almost 50% of the study group, Additionally, it is possible that the low SUA indicates either a loss of kidney function or an early stage of chronic kidney disease [83].…”
Section: Snapple -Kiwi Strawberrymentioning
confidence: 93%
“…Sodium bicarbonate (NaHCO 3 ) 2,000 mg twice daily has also been reported to increase urinary pH in diabetes type 1 adults and reduce uric acid crystallisation [82].…”
Section: Mineralsmentioning
confidence: 99%
“…Most of these diseases can be prevented by early administration of ULT [ 45 , 46 , 47 , 48 ]. Further studies suggested that intermittent uricosuria might result in tubular injury by both the direct toxic effects of urate crystals in tubules and the phenotypic transition of tubular cells induced by high concentrations of urate [ 7 , 11 , 49 ]. To date, it is believed that hyperuricemia is not only the result of renal impairment or sharing the risk factors with CKD, but also can be the cause of renal function impairment.…”
Section: Hyperuricemia and Renal Diseasementioning
confidence: 99%